PENGARUH PROGRAM LITERASI UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS 2 SDN KARANGNANGKA 1 - Aprilia, Nur Aini; Jamilah; M. Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify significant differences in the reading skills of grade II students of SDN Karangnangka I before and after participating in a literacy habituation program at school. This study uses a quantitative method with a pre-experimental one group pre-test post-test experimental design. The data in this study were obtained by giving an objective test of 15 questions to grade II students which were used as a measuring tool for students' reading skills before and after the literacy program treatment, namely as a pre-test and post-test. The pre-test results showed that students' reading skills were still very low as seen from the average pre-test score of 42.86. After being given treatment through literacy habituation in the form of literacy activities and literacy workshops, there was a significant increase in reading skills as indicated by the average post-test score of 69.00. The results of this study indicate that the literacy habituation program at school is indeed considered effective in improving students' reading skills for elementary school students, especially in lower grades, but requires consistency and support from various related parties.